Plasma and Urinary TMAO and Methylamine Responses to Meat and Egg Ingestion: Links to Gut Microbiota Composition in Subjects With and Without Metabolic Syndrome. - Hefni, Mohammed E.; Esberg, Anders; Hellström, Patrik; Johansson, Ingegerd; Witthöft, Cornelia M. (Nutrients, 2025)
Background/Objectives: Trimethylamine N-oxide (TMAO), a gut microbiota-derived metabolite from L-carnitine and choline (abundant in meat and eggs), is linked to CVD and T2D. This study investigated whether TMAO responses to animal-based foods differ between individuals with and without metabolic syndrome (MetS), in relation to their gut microbiota composition. Subjects/Methods: In a randomized crossover trial, 12 MetS (≥3 criteria according to the Adult Treatment Panel III: elevated waist circumference, fasting glucose, triglycerides, and blood pressure or reduced HDL cholesterol) and 21 non-MetS subjects consumed two test meals (3 hard-boiled eggs or 170 g meat balls) after overnight fasting, with ≥1-week washout. Blood was collected at baseline and 0.5, 1, 2, 4, and 6 h postprandially; urine was collected over 6 h. Fecal samples (collected pre-first day of intervention) underwent 16S rRNA sequencing. Plasma and urinary TMAO, TMA, choline, and carnitine were quantified using UPLC-MS/MS. Results: MetS subjects exhibited a non-significant trend towards higher incremental AUCs for plasma TMA, TMAO, choline, and carnitine after consuming both foods, with a 30–50% higher urinary TMAO excretion (but similar for TMA) versus non-MetS subjects. This exploratory analysis also indicated that MetS subjects had reduced gut microbial diversity, featuring decreased Blautia glucerasea (butyrate producer) and increased Ruminococcus torques (pro-inflammatory), a profile associated with inflammation but not TMA production. Conclusion: No significant increase in plasma methylamines after choline and carnitine challenge was observed in subjects with MetS compared with non-MetS. In MetS subjects (without CVD and T2D), gut microbiota composition was characterized by increased pro-inflammatory bacteria rather than TMAO-generating bacteria. The lack of statistical significance with regard to plasma TMAO response could be due to an insufficient sample size rather than the absence of an effect. Nevertheless, the observed elevation might still be clinically relevant, supported by concurrent differences in microbiota composition. These preliminary findings warrant validation in larger cohorts due to sample size limitations.